2017
DOI: 10.1080/10245332.2017.1318334
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship between vitamin D levels and platelet indices in Korean adults

Abstract: PC and MPV are inversely associated with vitamin D levels in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
5
26
1
1
Order By: Relevance
“…Our data show, for the first time, that subjects with lower 25(OH)D levels have higher platelet numbers, indicating that a vitamin D deficiency in obese subjects may be predictive of a higher risk of inflammation, thrombosis and cardiovascular events in this condition. These results are in line with previous findings by Park and colleagues, that showed an inverse association between 25(OH)D levels and platelet indices in the general adult population but did not investigate possible differences between healthy and unhealthy subjects [19]. To better explain the interrelationship between obesity, vitamin D, platelet count and cardiovascular risk, it is of note that vitamin D has a direct role in regulating hematopoietic cells' differentiation [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data show, for the first time, that subjects with lower 25(OH)D levels have higher platelet numbers, indicating that a vitamin D deficiency in obese subjects may be predictive of a higher risk of inflammation, thrombosis and cardiovascular events in this condition. These results are in line with previous findings by Park and colleagues, that showed an inverse association between 25(OH)D levels and platelet indices in the general adult population but did not investigate possible differences between healthy and unhealthy subjects [19]. To better explain the interrelationship between obesity, vitamin D, platelet count and cardiovascular risk, it is of note that vitamin D has a direct role in regulating hematopoietic cells' differentiation [21].…”
Section: Discussionsupporting
confidence: 91%
“…People affected by diabetes [15,16], coronary artery disease [17], endothelial dysfunction or Sjögren's syndrome [18], which are all triggering conditions for inflammation and higher levels of inflammatory markers, have been described to exhibit poor vitamin D status. However, Park et al recently showed an inverse association between 25(OH)D levels and platelet count in the general adult population, although they did not investigate possible differences between healthy and unhealthy subjects [19]. There is no information about whether this association exists in overweight subjects.…”
Section: Introductionmentioning
confidence: 99%
“…7 Previously, few studies investigated direct associations between vitamin D concentrations and platelet parameters in health and disease. [35][36][37][38][39][40] Verdoia et al reported an association between low vitamin D concentrations and high-residual platelet reactivity in patients with cardiovascular diseases receiving dual antiplatelet therapy, 35 and similarly this was shown in patients with diabetes. 38 Moreover, in hemodialysis patients vitamin D supplementation resulted in antithrombotic effects.…”
Section: Discussionmentioning
confidence: 77%
“…The evidence suggests that patients with vitamin D deficiency have a higher MPV and therefore a greater risk of vascular disease. Indeed, Parker and colleagues showed that vitamin D deficient patients had significantly higher MPV than those with adequate 25(OH)D 3 D3 levels [35]. Similarly, Korzonek-Szlacheta and colleagues found that the MPV in patients with 25(OH)D 3 levels >20 ng/mL was lower than that in patients with 25(OH)D 3 levels <10 ng/mL and in patients with 25(OH)D 3 levels comprised between 10 and 20 ng/mL [36].…”
Section: Discussionmentioning
confidence: 99%